2003
DOI: 10.1038/sj.onc.1206828
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-induced apoptosis in immortalized normal and malignant human ovarian surface epithelial cells involves enhanced expression of FasL

Abstract: Progesterone (P4) has been implicated as a protective factor for epithelial ovarian cancers, yet little is known about its mechanism of action. We previously reported that pregnancy-equivalent doses of P4 inhibited the growth of normal and malignant human ovarian surface epithelial (HOSE) cells. Here, we investigated how P4-induced cell death in two immortalized normal (HOSE 642, and two malignant (OVCA 429, OVCA 432) HOSE cell lines. The exposure of HOSE or OVCA cell cultures to 10 À6 m P4 induced time-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 55 publications
4
57
1
Order By: Relevance
“…First, EDD plays a pivotal role in the progesterone pathway, being both regulated by progestin and directly binding the progestin receptor and enhancing its transcriptional activity (Callaghan et al, 1998;Henderson et al, 2002). It has been known for several years that progesterone has a protective effect on ovarian cancer, the mechanism attributed to a reversal of the transformed phenotype including reduction of cyclin-dependent kinase activity and increased Fas/FasL-induced apoptosis (Blumenthal et al, 2003;Syed and Ho, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…First, EDD plays a pivotal role in the progesterone pathway, being both regulated by progestin and directly binding the progestin receptor and enhancing its transcriptional activity (Callaghan et al, 1998;Henderson et al, 2002). It has been known for several years that progesterone has a protective effect on ovarian cancer, the mechanism attributed to a reversal of the transformed phenotype including reduction of cyclin-dependent kinase activity and increased Fas/FasL-induced apoptosis (Blumenthal et al, 2003;Syed and Ho, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously described the origin and culture conditions of nontumorigenic human OSE cell lines (HOSEs) and OCa cell lines (OVCAs) used in this study (Syed et al, 2001(Syed et al, , 2002Syed and Ho, 2003). In short, three HOSE cell lines (HOSE 642, were derived from normal ovaries obtained from women with noncancer gynecologic indications, specifically a 46-year-old healthy woman, a 48-year-old with ovarian inclusion cysts in one ovary, and a 39-year-old patient with ovarian stromal hyperplasia, respectively.…”
Section: Cell Cultures and Cell Linesmentioning
confidence: 99%
“…A handful of studies have demonstrated that progestins inhibit cell growth and/or induce apoptosis in OCa cell cultures (Bu et al, 1997;Hu and Deng, 2000;Keith and Bonavida, 2001;Yu et al, 2001;Syed and Ho, 2003). Alterations in apoptosis regulators such as bcl-2, c-myc, and p53 were detected in OCa cells undergoing progestin-induced apoptosis (Bu et al, 1997;Hu and Deng, 2000;Athanassiadou et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, macaques treated with progestin exhibited upregulation of apoptosis in OSE cells (Rodriguez et al, 1998). Though the exact mechanism by which progesterone exhibits growth-inhibitory effects is not fullyunderstood, Syed and Ho (2003) demonstrated involvement of the caspase 8 Fas/FasL pathway in progesterone-mediated apoptosis in OSE. Culturing OSE in vitro with the inflammatory mediator IL-1 results in upregulation of several inflammation-associated genes, specifically HSD11B1, which plays a role in conversion of cortisone to cortisol (Rae et al, 2004b).…”
Section: Estrogen and Progesterone Signaling In Normal Ovarian Surfacmentioning
confidence: 99%